Primary school teacher education students' response to the use of Zoom meeting breakout rooms for small group discussions - Risdalina, Risdalina; Rosmalinda, Desy; Pamela, Issaura Sherly; J.M., Zareena (Jurnal Inovasi Teknologi Pendidikan, 2024)
Learning that is carried out in class should be student-centered learning. One of the ways of student-centered learning is small group discussions. Developing technology also contributes to the development of the world of education. Learning using the small group discussion method can be presented online using Zoom Meeting. This application provides the Breakout Rooms feature, allowing users to create separate additional rooms in one meeting session. Therefore, this study aims to determine how students respond to using Breakout Rooms at Zoom Meetings. The research was carried out at the Primary School Teacher Education Study Program, Jambi University, in the even semester of 2023. This research was conducted on 34 semester four students. Research subjects were selected using a cluster random sampling technique. This research is descriptive. Data was collected using a questionnaire given to students via Google Forms. The data were analyzed by calculating the percentage of each statement on aspects of student response. The results of student responses are that Breakout Rooms are easy to use, helpful in supporting the learning process, making learning fun, and making discussions more focused and productive.